The articulate advocate : new techniques of persuasion for trial lawyers - Johnson, Brian K. (Crown King Books, 2009)
What do I do with my hands? Aren't gestures distracting? How do I remember everything? I tend to talk so fast - how can I slow down? This handbook answers these questions. It teaches how to say and do it. It reveals techniques to help litigators look, sound, and feel natural and polished in the courtroom.